Digitalisasi dan Hukum Adat : Pemanfaatan Teknologi dalam Dokumentasi Hukum Adat - Arief Fahmi Lubis (Public Service and Governance Journal, 2022)
One of the important aspects of the digitization of customary law is the creation of a comprehensive digital database. The purpose of this study is to show that this approach not only results in richer and more authentic documentation, but also empowers communities to be active in the process of preserving their own culture. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study show that the digitization of customary law has great potential not only to preserve valuable cultural heritage, but also to revitalize and make customary law more relevant in facing the challenges of the 21st century.